2017
DOI: 10.25081/josac.2017.v26.i1.805
|View full text |Cite
|
Sign up to set email alerts
|

Volatile oil composition of four popular varieties of large cardamom (Amomum subulatum Roxb.)

Abstract: In the present study volatile oil profile of the four popular varities of large cardamom (Amomum subulatum Roxb.) namely Sawney, Varlangey, Ramla and Ramsey were studied in detail. The capsules contained 58.1-68.1% seeds and 1.2-2.8% essential oil. By GC-MS analysis 23 constituents of the oil were identified with 1, 8-cineole as the chief component. Major constituents of the oil were α-pinene (1.7-6.5%), β -pinene (4.0-11.1%), 1, 8-cineole (63.2-73.4%) and α-terpineol (5.6-7.6%). The oil contained high level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…This study is also supported by other groups [22,23]. The concentration and the percentage of the other components (α-pinene, β-pinene, terpineol, nerolidol, and limonene) were different from the previous reports [24]. This study is the 1 st time reported the chemical composition of Seremna and it was found higher than the other selected cultivars.…”
Section: Identification Of Active Metabolites In a Subulatum Cultivarssupporting
confidence: 82%
“…This study is also supported by other groups [22,23]. The concentration and the percentage of the other components (α-pinene, β-pinene, terpineol, nerolidol, and limonene) were different from the previous reports [24]. This study is the 1 st time reported the chemical composition of Seremna and it was found higher than the other selected cultivars.…”
Section: Identification Of Active Metabolites In a Subulatum Cultivarssupporting
confidence: 82%
“…The oil from dried aerial parts of green cardamom was hydrodistilled in all glass Clevenger-type apparatus for 3 h with 5.70% yield (42). Four different cultivars of black cardamom from Indian regions were used for oil extraction by hydrodistillation which presented 1.2-2.8% oil yield (43). Govindarajan et al (44) used modified Clevenger-type hydrodistillation apparatus to extract oil (0.73% yield) from fresh leaves of black cardamom for 3 h. Noumi et al (45) obtained green and black cardamom seed oils by hydrodistillation technique.…”
Section: Conventional Extraction Methodsmentioning
confidence: 99%